1979
DOI: 10.1002/art.1780220101
|View full text |Cite
|
Sign up to set email alerts
|

Tγ cells in systemic lupus erythematosus

Abstract: Circulating T cells bearing receptors for the Fc portion of IgC (T,) were identified by sensitive immunofluorescent techniques with rabbit IgG b4 allotype/antib4 complexes. A twofold decrease in both proportion and absolute number of T, cells was found in patients with active systemic lupus erythematosus (SLE) relative to values obtained during disease remission. The reduction in T, cells was most evident in patients with severe hypocomplementemia. A deficit of T, cells in active patients was not demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the last few years, the distribution pattern of these T lymphocyte subsets in various immunologically mediated diseases has been determined in some studies, unbalanced proportions of T cell subpopulations have been reported (3)(4)(5)(6)(7). For example, in rheumatoid arthritis (RA), Biberfield et a1 (8) detected an unbalanced TJ T, ratio in synovial fluid, while normal or increased T, cells were found in peripheral blood (PB) of patients compared to controls.…”
mentioning
confidence: 99%
“…In the last few years, the distribution pattern of these T lymphocyte subsets in various immunologically mediated diseases has been determined in some studies, unbalanced proportions of T cell subpopulations have been reported (3)(4)(5)(6)(7). For example, in rheumatoid arthritis (RA), Biberfield et a1 (8) detected an unbalanced TJ T, ratio in synovial fluid, while normal or increased T, cells were found in peripheral blood (PB) of patients compared to controls.…”
mentioning
confidence: 99%